First-birth Timing, Marital History, and Women's Health at Midlife. (December 2015) - Williams, Kristi; Sassler, Sharon; Addo, Fenaba; Frech, Adrianne
Despite evidence that first-birth timing influences women's health, the role of marital status in shaping this association has received scant attention. Using multivariate propensity score matching, we analyze data from the National Longitudinal Survey of Youth 1979 to estimate the effect of having a first birth in adolescence (prior to age 20), young adulthood (ages 20–24), or later ages (ages 25–35) on women's midlife self-assessed health. Findings suggest that adolescent childbearing is associated with worse midlife health compared to later births for black women but not for white women. Yet, we find no evidence of health advantages of delaying first births from adolescence to young adulthood for either group. Births in young adulthood are linked to worse health than later births among both black and white women. Our results also indicate that marriage following a nonmarital adolescent or young adult first birth is associated with modestly worse self-assessed health compared to remaining unmarried.